The Role of BDNF on Neural Plasticity in Depression - Yang, Tao; Nie, Zheng; Shu, Haifeng; Kuang, Yongqin; Chen, Xin; Cheng, Jingmin; Yu, Sixun; Liu, Huiying (Frontiers in Cellular Neuroscience, 2020)
Recent studies combining pharmacological, behavioral, electrophysiological and molecular approaches indicate that depression results from maladaptive neuroplastic processes occurring in defined frontolimbic circuits responsible for emotional processing such as the prefrontal cortex, hippocampus, amygdala and ventral striatum. Meanwhile, the role of the brain-derived neurotrophic factor and the other neurotrophins in the pathophysiology of depression is well known. The abnormal neural plasticity in depression may be related to alterations in the levels of neurotrophic factors, which play a central role in plasticity. Enhancement of neurotrophic factors signaling has great potential in therapy for depression. This review highlights the relevance of neurotrophic factors mediated neural plasticity and pathophysiology of depression. These studies reviewed here may suggest new possible targets for the pharmacotherapy of depression such as neurotrophic factors, their receptors and related intracellular signaling cascades, and agents facilitating the activation of gene expression and increasing the transcription of neurotrophins in the brain.